2017
DOI: 10.3390/atmos8030047
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Composition, and Mixing State of Individual Aerosol Particles in Northeast China during Wintertime

Abstract: Northeast China is located in a high latitude area of the world and undergoes a cold season that lasts six months each year. Recently, regional haze episodes with high concentrations of fine particles (PM 2.5 ) have frequently been occurring in Northeast China during the heating period, but little information has been available. Aerosol particles were collected in winter at a site in a suburban county town (T1) and a site in a background rural area (T2). Morphology, size, elemental composition, and mixing stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Similar results that secondary aerosol formation causes heavy winter hazes in the NCP have been well documented (Y. Sun et al, 2014;Xue et al, 2016;. Because of low O 3 levels at 12 ppb (Fig.…”
Section: Sources and Formation Of Two Distinctive Haze Eventssupporting
confidence: 82%
“…Similar results that secondary aerosol formation causes heavy winter hazes in the NCP have been well documented (Y. Sun et al, 2014;Xue et al, 2016;. Because of low O 3 levels at 12 ppb (Fig.…”
Section: Sources and Formation Of Two Distinctive Haze Eventssupporting
confidence: 82%
“…Li et al (2012) found a large number of spherical POA particles in a coal-burning area over the China Loess Plateau during the winter heating period. POA particles were the most abundant in winter at the rural site in Northeast China (Xu et al, 2017). Moreover, some studies noted that the concentrations of organic particles from emissions of industrial boiler and coal-fired power plants were far lower than those from coal and biomass burning in residential stoves (Liu et al, 2016;Zhang et al, 2008).…”
Section: Sources Of Organic Particlesmentioning
confidence: 99%
“…These secondary particles are mainly composed of element C, O, S and minor N and are defined as S-rich particles [18,20]. We infer that they indeed are mixtures of sulfate, nitrate, and/or organic matter (OM) in the atmosphere [18].…”
Section: Nature Of Individual Aerosol Particlesmentioning
confidence: 91%
“…Elemental composition was semi-quantitatively determined by energy-dispersive X-ray spectrometer (EDX) with a spectral acquisition time of~30 s and elements heavier than C (Z ≥ 6) can be detected [20]. Copper (Cu) was not included from our analysis because the TEM grids were made of Cu.…”
Section: Tem Analysismentioning
confidence: 99%